Blockchain Based Software Development for Digital Identity Management Systems - Ethan Tan; Sofia Linm; Arnes Yuli Vandika (Journal of Moeslim Research Technik, 2024)
The increasing prevalence of digital identities has raised concerns about security, privacy, and data ownership. Traditional identity management systems often lack transparency and are vulnerable to breaches, necessitating more secure alternatives. Blockchain technology offers a decentralized approach that can enhance the security and integrity of digital identity management. This research aims to develop a blockchain-based software solution for digital identity management systems. The study focuses on creating a secure, user-centric platform that allows individuals to control their personal information while ensuring data integrity and privacy. A design-based research approach was employed, involving the development of a prototype using Ethereum blockchain technology. The system architecture was designed to facilitate secure identity verification and data storage. User testing was conducted to evaluate usability and effectiveness, with feedback collected through surveys and interviews. The prototype demonstrated significant improvements in security and user control over personal data. Key features included decentralized storage of identity information, smart contracts for verification processes, and enhanced privacy measures. User feedback indicated a high level of satisfaction with the system's usability and perceived security. The research concludes that blockchain technology presents a viable solution for digital identity management, offering enhanced security and user control. The developed software prototype demonstrates the potential for broader applications in various sectors, paving the way for future research to explore scalability and integration with existing identity management frameworks.